Evaluation of a Pilot Parent-Delivered Play-Based Intervention for Children With Attention Deficit Hyperactivity Disorder - Wilkes-Gillan, S.; Bundy, A.; Cordier, Reinie; Lincoln, M. (American Occupational Therapy Association, Inc, 2014)
Objective: This study evaluated a parent-delivered intervention aiming to address the social difficulties of children with attention deficit hyperactivity disorder (ADHD). The intervention was evaluated from three perspectives: effectiveness, feasibility, and appropriateness. Method: This one-group pretest–posttest study included 5 children with ADHD and their parents, who had previously participated in a therapist-delivered play-based intervention. The 7-wk parent-delivered intervention involved home modules (including a DVD, manual, and play dates with a typically developing playmate) and three therapist-led clinic-based play sessions. The Test of Playfulness was used as a pre- and postintervention and follow-up measure. Parents were interviewed 1 mo following the intervention, and data were analyzed for recurring themes. Results: Children’s social play outcomes improved significantly from pretest to 1-mo follow-up (Z = 2.02, p = .04, d = 1.0). Three themes emerged: the clinic play environment as a sanctuary, parental barriers to intervention delivery, and tools for repeating learned lessons. Conclusion: The parent-delivered intervention demonstrated preliminary evidence for feasibility and effectiveness. Further research is warranted regarding appropriateness.